ANALISIS PENGALAMAN PENGGUNA ENTERPRISE RESOURCE PLANNING DENGAN FRAMEWORK USER EXPERIENCE QUESTIONNAIRE (STUDI KASUS: UNIVERSITAS MULTIMEDIA NUSANTARA) - CK, Andrei Ferdinan Bayu; Setiawan, Johan (Journal of Multidisciplinary Issues, 2021)
ERP or Enterprise Resource Planning is a design that has been applied in an educational institution or company that can be used to organize, coordinate and manage the system resources in it to be more integrated. The refusal of system users to use the ERP system (new system) is one of the failure factors for ERP system implementation that should be considered by higher education companies. User's lack of understanding by users can cause users to simply be forced to use without being adapted to a qualified use of the ERP system. In addition to the importance of the ERP implementation process in a company or university, there is also an influence on the system's user experience as the key to the success of ERP implementation to minimize failures in the ERP system process. This study uses the User Experience Questionnaire Framework to analyze, measure and find out significantly how much influence the user experience level has on the PeopleSoft Oracle Campus Solution ERP system using the six aspects contained in the framework UEQ on the modules Student Record, Academic Advisement, and Student Financial in the respective departments at UMN. The research was conducted quantitatively, namely the collection and collection of data to be carried out through the distribution of questionnaires online and carried out using SPSS software. The results of the measurement level obtained based on the mean and benchmark data user experience from the six UEQ scales from the highest to the lowest value level are Dependability is in the category (Excellent), Stimulation is in the category (Excellent), Novelty is in the category (Excellent), Perspicuity category is in the category (Good), Attractiveness is in the category (Good), and Efficiency is in the category (Good) and partially or completely can have a significant 61% influence on the use of modules in the ERP system at UMN. Keywords: ERP (Enterprise Resource Planning), UEQ (User Experience Questionnaire), Quantitative, SPSS.